Mechanical and thermal transmission properties of carbon nanofibre-dispersed carbon/phenolic multiscale composites - Bhattacharyya, A. (2013)
The present article reports the development and characterization of carbon nanofiber (CNF)-incorporated carbon/phenolic multiscale composites. Vapor-grown CNFs were dispersed homogeneously in to phenolic resin using an effective dispersion route, and carbon fabrics were subsequently impregnated with the CNF-dispersed resin to develop carbon fiber/CNF/phenolic resin multiscale composites. Mechanical and thermal transmission properties of multiscale composites were characterized. Elastic modulus and thermal conductivity of neat carbon/phenolic and multiscale composites were predicted and compared with the experimental results. It was observed that incorporation of only 1.5 wt % CNF resulted in 10% improvement in Young’s modulus, 12% increase in tensile strength, and 36% increase in thermal conductivity of carbon/phenolic composites. Fracture surface of composite samples revealed the formation of stronger fiber/matrix interface in case of multiscale composites than neat carbon/phenolic composites. Enhancement of above properties through CNF addition has been explained, and the difference between the predicted values and experimental results has been discussed.